Sex determination by amplification of amelogenin gene from dental pulp tissue by polymerase Chain Reaction - Ripon Md Chowdhury; Abhishek Singhvi; Neeta Bagul; Sanya Bhatia; Gurdeep Singh; Surajit Goswami (Wolters Kluwer Medknow Publications, 2018)
Introduction: Forensic odontology necessarily involves the application of dentistry along with various other branches of sciences which deals with proper handling, examination, evaluation, and presentation of dental evidences, that aids to investigate a crime and deliver justice. Sex determination is a part of forensic odontology and an essential priority when traditional identification of the deceased becomes impossible. Aim: To determine Sex by analysis of the Amelogenin gene using Polymerase Chain Reaction (PCR) method on Deoxyribose nucleic acid (DNA) isolated from dental pulp, which was exposed to various environmental conditions created artificially to mimic a forensic scenario. Materials and Method: This in-vitro study was conducted by subjecting extracted teeth to various conditions imitating a forensic scene, viz. desiccation at room temperatures, immersion in salt water, burial in soil and even exposing to extremes of temperatures. DNA was extracted from dental pulp tissue and sex determination was achieved by amplification of the amelogenin gene through AMEL gene based primers in PCR. Result: Among all the samples used in this study, DNA could be extracted from all, except from those that were subjected to a temperature of 350 °C. DNA amplification and sex determination of the samples were found to be accurate when compared to sex of the individual which was recorded initially, during collection of teeth samples. Conclusion: This study shows teeth to be a potent source of DNA even in extreme environmental conditions, barring high temperatures and determination of sex by PCR amplification of AMEL markers to be quite reliable.